Nutritional Enhancement of Traditional Indian Snacks with Oilseed Meal Incorporation - Karnika,; , Asha kawatra (Archives of Current Research International, 2025)
Background: India faces significant challenges with hunger and malnutrition, despite being a major producer of oilseed meals. These meals, byproducts of oil extraction, are rich in nutrients but underutilized for human consumption. Aim: This study aimed to develop nutrient-dense versions of the traditional Indian snacks, mathi and sev, by incorporating different oilseed meals, thereby addressing nutritional deficiencies and promoting the utilization of these byproducts. Methodology: Groundnut meal, sesame meal, and flaxseed meal were incorporated individually and in composite form into mathi and sev recipes at 12%, 18%, and 24% levels. A panel of semi-trained judges conducted organoleptic evaluations and found that 24% of the products were acceptable; further evaluation was carried out on those products. The nutritional properties, including proximate composition, antioxidant activity, phytic acid content, and in vitro protein digestibility, were analyzed of 24% level products. The shelf life of the developed products was also assessed. Results: The incorporation of oilseed meals enhanced the nutritional profile of both mathi and sev. All developed products were organoleptically acceptable. Conclusion: Oilseed meals can be effectively utilized to develop nutrient-dense traditional Indian snacks. These products have the potential to improve nutritional status and reduce malnutrition within communities.